A glimpse into the biogeography, seasonality, and ecological functions of arctic marine Oomycota - Brandon T. Hassett; Marco Thines; Anthony Buaya; Sebastian Ploch; R. Gradinger (IMA Fungus)
Abstract High-latitude environments are warming, leading to changes in biological diversity patterns of taxa. Oomycota are a group of fungal-like organisms that comprise a major clade of eukaryotic life and are parasites of fish, agricultural crops, and algae. The diversity, functionality, and distribution of these organisms are essentially unknown in the Arctic marine environment. Thus, it was our aim to conduct a first screening, using a functional gene assay and high-throughput sequencing of two gene regions within the 18S rRNA locus to examine the diversity, richness, and phylogeny of marine Oomycota within Arctic sediment, seawater, and sea ice. We detected Oomycota at every site sampled and identified regionally localized taxa, as well as taxa that existed in both Alaska and Svalbard. While the recently described diatom parasite Miracula helgolandica made up about 50% of the oomycete reads found, many lineages were observed that could not be assigned to known species, including several that clustered with another recently described diatom parasite, Olpidiopsis drebesii. Across the Arctic, Oomycota comprised a maximum of 6% of the entire eukaryotic microbial community in Barrow, Alaska May sediment and 10% in sea ice near the Svalbard archipelago. We found Arctic marine Oomycota encode numerous genes involved in parasitism and carbon cycling processes. Ultimately, these data suggest that Arctic marine Oomycota are a reservoir of uncharacterized biodiversity, the majority of which are probably parasites of diatoms, while others might cryptically cycle carbon or interface other unknown ecological processes. As the Arctic continues to warm, lower-latitude Oomycota might migrate into the Arctic Ocean and parasitize non-coevolved hosts, leading to incalculable shifts in the primary producer community.